Preparation of Functional Coating Films Using Breath Figure (Bf) Method and the Study of Morphological, Optical and Wettability Behavior with Varying Experimental Conditions - Sanchez-Poblete, J; Alavia-Medina, W; Martin-Trasancos, R; Martin-Trasancos, R; Boulett-Neira, A; Boulett-Neira, A (Taylor and Francis Ltd., 2023)
In this work, photoactive polymer film coatings were prepared using the breath figure (BF) method, starting from a poly(tert-butyl acrylate-styrene block), PtBA-block-PS and a photochromic agent, 1-(2-hydroxyethyl)-3,3-dimethylindoline-6-nitrobenzopyran (SP) grafted onto the poly(tert-butyl acrylate) block. The effects upon the composite film behavior in response to the solvent concentration, type of solvent and relative humidity were studied. Films containing homogeneously dispersed micrometre-sized pores were obtained. The optical and morphological behavior were investigated using optical microscopy and scanning electron microscopy. The films obtained have various potential applications as surface coating materials with color changing properties, such as whiteboards, device displays or advertising surfaces. © 2023 Taylor & Francis Group, LLC.
Keywords: Material chemistry; photo-optical switching components; morphological analysis; polymer porous films; porous organic polymers